Transfer of blaTEM gene between Salmonella and Escherichia coli under processing conditions of animal products: influence of a copper(II) complex - Ribeiro, Rosanne Aparecida Capanema; Guidotti-Takeuchi, Micaela; Dumont, Carolyne Ferreira; Buiatte, Ana Beatriz Garcez; de Araújo Brum, Bárbara; Martins, Thais Jansen; Ramos, Luana Munique Sousa; Guerra, Wendell; Polveiro, Richard Costa; de Melo, Roberta Torres; Rossi, Daise Aparecida (Frontiers in Microbiology, 2025)
The high prevalence of infections caused by contaminated food, coupled with growing antimicrobial resistance, especially through horizontal gene transfer, is a challenge for public health worldwide. It is possible that this situation is intensified in the presence of by-products from animal product processing industries. In view of this, we investigated the horizontal transfer of the blaTEM gene from S. Heidelberg to E. coli J53 AzR, in the absence and presence of whey (WH) and chicken juice (CJ) in: (i) liquid medium for 3 h under agitation; (ii) solid medium overnight; (iii) liquid medium overnight and the influence of the copper(II) complex Lu54 in mitigating this transfer. The first protocol showed the highest relative conjugation frequency (RCF) of 2.23% in the absence of supplements and increased by three and four orders of magnitude in the presence of CJ and WH and was selected for treatment with Lu54. In solid/overnight, there were RCFs of less than 1%, while the liquid/overnight medium showed RCFs higher than the first protocol only in WH. The presence of WH acidified the medium, which resulted in higher RCF. Lu 54 reduced RCF from 2.2 to 0.3%, 8.2 to 1.7% and 6.2 to 0.9%, respectively, for the tests without by-products and with WH and CJ. In addition, the genomes were sequenced to map the blaTEM gene and β-lactamase families in transconjugants. The results showed that three plasmids containing blaTEM were detected in the controls and the same gene was not identified in the treatments, suggesting plasmid loss induced by the copper(II) complex (Lu54). The results prove that WH and CJ increase the frequency of conjugation in liquid media, and the Lu54 complex is a promising alternative to mitigate conjugation and, consequently, the spread of antimicrobial resistance, especially in milk and meat processing industries.